Corporat E Social Responsibility And Its Impact To The Financial Performance: Study On Financial Industry In Malaysia From The Perspectives Of Stakeholders - Mohd Fathanah, Shukri Saghiri (2022)
Corporate Social Responsibility (“CSR”) is a self-regulating business model that assists a corporation in being socially accountable to itself, its stakeholders, and the public. Companies that practice CSR, also known as corporate citizenship, can be aware of the impact they are having on all parts of society, including the economic, social, and environmental. CSR has improved corporate image, boosted sales and market share, reinforced brand positioning, increased ability to recruit and retain personnel, decreased operation expenses, and increased appeal to investors, as well as having an impact on the company’s financial performance. The main objective of this research is to study the significant impact of CSR activities on four groups of stakeholders, namely Employee, Customer, Supplier and Community which are linked to the financial performance of a company. In this research study, 200 sets of questionnaires were prepared and distributed to the targeted respondents working in Kuala Lumpur and Selangor. However, due to the Covid19 restrictions and tight deadline for submission, only 108 respondents had answered the questionnaires. After the data were collected, Statistical Package for the Social Sciences (SPSS) was used to test the data in order to generate the final result. In the end, the final result shows that there is significant impact of CSR activities on four group of stakeholders that is linked to the financial performance of a company